b-5(b+1)-3=-(8+4b)

Simple and best practice solution for b-5(b+1)-3=-(8+4b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b-5(b+1)-3=-(8+4b) equation:



b-5(b+1)-3=-(8+4b)
We move all terms to the left:
b-5(b+1)-3-(-(8+4b))=0
We add all the numbers together, and all the variables
b-5(b+1)-(-(4b+8))-3=0
We multiply parentheses
b-5b-(-(4b+8))-5-3=0
We calculate terms in parentheses: -(-(4b+8)), so:
-(4b+8)
We get rid of parentheses
-4b-8
Back to the equation:
-(-4b-8)
We add all the numbers together, and all the variables
-4b-(-4b-8)-8=0
We get rid of parentheses
-4b+4b+8-8=0
We add all the numbers together, and all the variables
=0
b=0/1
b=0

See similar equations:

| 5x–13=2x–1 | | (h-2)6²=9 | | 230=161-w | | 3x=1/3=2/3 | | 1.7=10/x | | 1500000+x=50000+20000+143000+.x+1800000 | | 3z+25=3.2+3z | | 8-5(x-6)=35-5x | | m=-8b=-6 | | m=8b=-6 | | 5x+1+×+11=90 | | 7z-10z=18 | | 7m+25=32 | | 3(1+2u)= | | 70-40p= | | -7-5m=-(4+5m) | | 6r+72=683.88 | | 15=3(b−12) | | 144+x^2=900 | | y+40/3=5 | | 3+7v=25 | | 5s+20=85 | | -4.42+g=5.58 | | 360=138+x/2 | | 16-2=2n-25 | | 3+2+5x-x+12= | | u^2-13u=36 | | 9.6+x=2.3 | | 2h=15.86 | | -4n-1=2n-55 | | C=5n+40  | | (6x-5)+(x+5)+(2x-3)=180 |

Equations solver categories